A numerical method for evaluating the torque efficiency of hydraulic orbit motors considering deformation effects and frictional losses. (1st January 2021) - Manne, Venkata Harish Babu; Vacca, Andrea; Merrill, Kyle
Highlights: The proposed simulation model evaluates torque efficiency of hydraulic orbit motors. The model considers deformation effects and frictional losses of the hydraulic motor. Both the torque pulsation and the mechanical efficiency are experimentally validated. The simulated torque agrees with the measurements. The micro-motion of rotor, subjective to forces, is evaluated numerically. Abstract: This article presents a method for evaluating the torque output of orbit type displacement machines. Orbit machines are commonly used as hydraulic motors, for applications involving low speed and high torque output. The evaluation of the actual shaft torque as well as the hydro-mechanical efficiency in positive displacement machines is a topic that still presents challenges related to the evaluation of the torque losses associated with the functioning of the unit. This paper proposes a method of evaluating the torque efficiency starting from the evaluation of the instantaneous pressurization of each displacement chamber through a lumped parameter approach. From the instantaneous pressure in each chamber of the orbit motor, the contact forces normal to the rotor profiles are evaluated using a contact mechanics formulation accounting for the energy dissipation. The proposed algorithm computes the friction losses at the contact points to evaluate the net torque output of the orbit motor. Besides accounting for the frictional losses, the main elements of novelty of this approach also include the evaluation of the component deformation, instead of making rigid body assumptions. Experiments are performed on a set of reference orbit motor units to evaluate the torque output at different operating conditions. A good agreement between the simulated output torque and the one measured from experiments was observed, in terms of both instantaneous and mean values. The corresponding comparison of mechanical efficiency map is also presented. This shows the potential of the proposed method, which can potentially be extended to other types of gear machines, to evaluate the net shaft torque.